2019
DOI: 10.1177/0020720919876815
|View full text |Cite
|
Sign up to set email alerts
|

Introducing systems theory with virtual laboratories at the University of Extremadura: How to improve learning in the lab in engineering degrees

Abstract: Virtual laboratories have been demonstrated to contribute successfully to the theoretical understanding of many important systems theory and automatic control concepts in engineering education. This paper describes the pilot experience on the use of such laboratories as learning tools in introductory systems theory courses at the University of Extremadura during the academic year 2015/2016. The purpose of the present paper is to offer some objective academic evidence for the effectiveness of the use of virtual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…After the experimentation with the mixed reality laboratory, a survey was applied to the students to measure their motivation regarding this laboratory. The formulation of the survey questionnaire was based on similar work on remote control laboratories (Achuthan et al, 2021;Liang & Liu, 2018;Tejado et al, 2021). The reliability of the questionnaire used was validated in previous studies (Achuthan et al, 2021), using the Cronbach's Alpha method and the instrument was found to be reliable (𝛼 > 0.79).…”
Section: Implementation With Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the experimentation with the mixed reality laboratory, a survey was applied to the students to measure their motivation regarding this laboratory. The formulation of the survey questionnaire was based on similar work on remote control laboratories (Achuthan et al, 2021;Liang & Liu, 2018;Tejado et al, 2021). The reliability of the questionnaire used was validated in previous studies (Achuthan et al, 2021), using the Cronbach's Alpha method and the instrument was found to be reliable (𝛼 > 0.79).…”
Section: Implementation With Studentsmentioning
confidence: 99%
“…The rise of virtual and remote laboratories is removing the limitations of traditional handson laboratories (Li et al, 2020;Macías García et al, 2020;Morales-Menendez et al, 2019;Tejado et al, 2021). Among these laboratories, those that use mixed reality and augmented reality laboratories have demonstrated several advantages over others because they combine the benefits of physical and virtual components (Liang & Liu, 2018;Zata et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Engineering education combines, in a balanced way, traditional lecture-style methods together with practical learning (refer to Tejado et al 4 for a review on current trends). Several methodologies became very popular to interconnect theory and practice, which can be mainly divided into three from the view-point of the type of laboratory used: approaches with hands-on laboratories, by means of remote laboratories, or with virtual ones.…”
Section: Introductionmentioning
confidence: 99%